PENGARUH CITRA MEREK, DESAIN PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK PERSEBAYA STORE DI SURABAYA - Khoirul, Muhammad; Maduwinarti, Ayun; Pujianto, Agung (Universitas 17 Agustus 1945 Surabaya, 2020)
Nowadays, Indonesian soccer in the modern era has begun to move forward into a large industry. Persebaya Surabaya is also known as one of the biggest clubs in Indonesia with the enthusiasm of its supporters. Until finally Persebaya succeeded in opening